Mapping the policy process in Nigeria: Examining linkages between research and policy - Aberman, Noora-Lisa; Schiffer, Eva; Johnson, Michael E.; Oboh, Victor (International Food Policy Research Institute, 2010)
How research contributes to the policy process in developing countries in general, and in Nigeria more specifically, is not well understood. Yet such understanding is a critical part of doing effective policy research. This has become especially critical for the International Food Policy Research Institute (IFPRI), which has set up a country office for policy research in Nigeria. A key challenge for IFPRI, and other research organizations in the country, is how to better integrate research results into policy and communicate research results to Nigerian policymakers. To gain some useful insights into how research does, or does not, influence policy in Nigeria, we examined a case involving the process leading up to the adoption in 2006 of Nigeria's National Fertilizer Policy. Rather than focusing on how research influences policy in general, examining a particular policy allowed us to trace the actual policy process that took place, the actors involved, and the types of links and interactions between them. A diverse group of stakeholders (government, donors, the research community, farmer organizations, and the private sector) undoubtedly debated the content of the fertilizer policy. Thus, its successful formulation and adoption offered a useful opportunity to examine how it came about in spite of competing vested interests (both for and against it) and what role, if any, research-based information played in developing it. The policy covered some highly contentious political issues, most prominently the issue of privatization of the fertilizer sector in place of the large-scale and long-standing subsidy program. How the actors engaged and appeased people with vested interests who would normally oppose the policy, and the degree to which research-based information played a role in policy development, is of interest to IFPRI and others engaged in policy research. To study the policy process that led to the formulation and adoption of the National Fertilizer Policy, we used a network-mapping tool, Net-Map. Drawing on social network approaches, the tool is particularly suitable since it can help highlight the actors and formal and informal interactions involved in the policy process, as well as examine the flows of information from researchers to help determine the pathways of research-based information. In support of the Net-Map method, we also undertook a content analysis of published and grey literature on fertilizer policies in Nigeria in the years prior to the passing of the fertilizer bill. This provided a context for the knowledge-based and policy discussions, who was involved in them, and who funded or drove them.